The Effect of Work Motivation and Organizational Culture on Employee Performance at PT. Telkom Padang Branch - Benny Ahmad Yusuf; Rini Sarianti; Chichi Andriani (Greenation Research & Yayasan Global Resarch National, 2023)
This study aims to analyze the influence of Work Motivation and Organizational Culture on Employee Performance of PT. Telkom Padang branch . This research was conducted at PT. Telkom Padang branch . The population in this study were all employees of PT. Telkom Padang branch totaling 142 people . The sampling technique used was a proportional cluster sampling technique so that a sample of 79 people was obtained. The data analysis technique used is regression analysis . Hypothesis testing in this study was carried out with the f test and t test. The results of the study show that : (1) Work motivation has a significant positive effect on Employee Performance at PT Telkom Padang branch , (2) Organizational Culture has a significant positive effect on Employee Performance at PT Telkom Padang branch .